The European economy in 1998 and 1999 - CPB Netherlands Bureau for Economic Policy Analysis (The Hague); Institut fur Weltwirtschaft (Kiel); National Institute of Economic; Social Research (London); Observatoire Français des Conjonctures Economiques (Paris); Prometeia (Bologna) (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
World economic activity remains relatively robust, although the Asian crisis casts a shadow over the picture. The rate of growth of world trade has slowed down since last fall, but is expected to remain above its trend level. International price developments remain quite moderate. Oil prices have declined substantially, and are among the lowest of the decade. Inflationary pressures are also limited in the industrial countries, as capacity constraints are not yet significant there and excess supply has materialized worldwide. The industrial countries show a sustained growth rate between 2Vi and 3 per cent on average. However, the combination of strong growth and low inflation is the result of divergent developments between countries. The US economy has been until recently particularly buoyant, as strong domestic demand has more than offset the dampening effect of falling exports to Asia. The Japanese economy remains in the doldrums. The threat of a deflation has recently prompted a substantial stimulation programme aiming at preventing a further deterioration of confidence. Êconomic growth in Asia has been-severely_ restricted, in particular in the ASEAN countries and Korea, although extensive rescue operations have brought the situation in the worst hit countries more or less under control. The impact on the European countries is as yet rather limited, as negative trade effects are largely compensated for by beneficial effects of lower imported inflation and lower interest rates. Thus Western Europe is in a position to sustain the recovery that began in mid-1996. Prospects have been strengthened as uncertainties associated with the implementation of the EMU have now been dissipated. The time has now come to begin to view the EMU countries as a single entity from the viewpoint of economic management, even if differences persist in many fields.
Keywords: 330